Africa's informal workers Collective agency, alliances and transnational organizing in urban Africa - Lindell, Ilda (Africa Now, 2010)
Africa's Informal Workers is a vigorous examination of the informalization and casualization of work, which is changing livelihoods in Africa and beyond. Gathering cases from nine countries and cities across sub-Saharan Africa, and from a range of sectors, this volume goes beyond the usual focus on household 'coping strategies' and individual agency, addressing the growing number of collective organizations through which informal workers make themselves visible and articulate their demands and interests. The emerging picture is that of a highly diverse landscape of organized actors, providing grounds for tension but also opportunities for alliance. The collection examines attempts at organizing across the formal-informal work spheres, and explores the novel trend of transnational organizing by informal workers. Part of the ground-breaking Africa Now series, Africa's Informal Workers is a timely exploration of deep, ongoing economic, political and social transformations.